Human ApoD, an apolipoprotein up-regulated in neurodegenerative diseases, extends lifespan and increases stress resistance in Drosophila - Muffat, Julien (National Academy of Sciences, 2008)
Apolipoprotein D (ApoD) expression increases in several neurological disorders and in spinal cord injury. We provide a report of a physiological role for human ApoD (hApoD): Flies overexpressing hApoD are long-lived and protected against stress conditions associated with aging and neurodegeneration, including hyperoxia, dietary paraquat, and heat stress. We show that the fly ortholog, Glial Lazarillo, is strongly up-regulated in response to these extrinsic stresses and also can protect in vitro-cultured cells in situations modeling Alzheimer's disease (AD) and Parkinson's disease (PD). In adult flies, hApoD overexpression reduces age-associated lipid peroxide accumulation, suggesting a proximal mechanism of action. Similar data obtained in the mouse [Ganfornina, M.D., et al., (2008) Apolipoprotein D is involved in the mechanisms regulating protection from oxidative stress. Aging Cell 10.1111/j.1474-9726.2008.00395.] as well as in plants (Charron et al., personal communication) suggest that ApoD and its orthologs play an evolutionarily conserved role in response to stress, possibly managing or preventing lipid peroxidation.